A weird equation

This is a really hard functional equation by me:

Find all \(f: \mathbb{R} \rightarrow \mathbb{R}\) such that

f(x2+f(y)2)=xf(x)+yf(y) f(x^2+f(y)^2)=xf(x)+yf(y) for all x,yRx,y \in \mathbb{R}

It looks quite simple but it's very difficult. Good luck if you try it!

Note by Wen Z
4 years, 6 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Some preliminary observations that might be useful. Will post more things as I keep progressing through.

Switch xx and yy around to get

f(x2+f(y)2)=xf(x)+yf(y)=f(y2+f(x)2)f(x^2+f(y)^2)=x f(x)+y f(y) = f(y^2 + f(x)^2)

Substitute y=0y=0 to get

f(x2+f(0)2)=f(f(x)2)f(x^2+f(0)^2)=f(f(x)^2)

Sharky Kesa - 4 years, 5 months ago

simple observations reveals f(x)=x

hiroto kun - 4 years, 5 months ago

Log in to reply

Find all means Find all and prove that you have all of them

Wen Z - 4 years, 3 months ago

Browsing old problems on Sharvil's feed...

Sub x=y=0x=y=0 to get f(f(0)2)=0f(f(0)^2)=0, and then sub y=f(0)2y=f(0)^2 to get f(x2)=xf(x)f(0)=0f(x^2)=xf(x)\Longrightarrow f(0)=0. Now subbing x=f(t),y=0x=f(t),y=0 gives f(f(t)2)=f(t)f(f(t))f(f(t)^2)=f(t)f(f(t)). But subbing x=0,y=tx=0,y=t gives f(f(t)2)=tf(t)f(f(t)^2)=tf(t). So if f(t)0f(t)\neq 0, then f(f(t))=tf(f(t))=t.

Now suppose f(u)0f(u)\neq 0 for some uu. Since f(u2)=uf(u)f(u^2)=uf(u) and clearly u0u\neq 0, we have f(u2)0f(u^2)\neq 0. Hence, f(f(u2))=u2f(f(u^2))=u^2. But recall f(u2)=uf(u)=f(f(u)2)f(u^2)=uf(u)=f(f(u)^2), so u2=f(f(f(u)2))u^2=f(f(f(u)^2)). Clearly f(f(u)2)0f(f(u)^2)\neq 0 otherwise u=0u=0, so f(f(f(u)2))=f(u)2f(f(f(u)^2))=f(u)^2, and thus f(u)=±uf(u)=\pm u. So

f(x)={xx0f(x)=\begin{cases}x\\-x\\0\end{cases}

for each xRx\in \mathbb{R}.

Now suppose f(u)=0f(u)=0 for some u0u\neq 0. Then subbing x=ux=u gives f(u2+f(y)2)=yf(y)f(u^2+f(y)^2)=yf(y) for all yRy\in \mathbb{R}. If f(y)0f(y)\neq 0 for some yy, we would have f(y)=±yf(y)=\pm y and thus yf(y)=±y20yf(y)=\pm y^2 \neq 0 so that f(u2+f(y)2)=±(u2+f(y)2)f(u^2+f(y)^2)=\pm \left(u^2+f(y)^2\right), and u2+f(y)2=±y2u=0u^2+f(y)^2=\pm y^2\Longrightarrow u=0 or u2=y2<0u^2=-y^2<0, a contradiction. So f(y)=0f(y)=0 for all yRy\in \mathbb{R}.

Finally, suppose f(u)=uf(u)=u and f(v)=vf(v)=-v for some u,v0u,v\neq 0. Then subbing x=u,y=vx=u,y=v gives f(u2+v2)=u2v20±(u2+v2)=u2v2u=0f(u^2+v^2)=u^2-v^2\neq 0\Longrightarrow \pm \left(u^2+v^2\right)=u^2-v^2\Longrightarrow u=0 or v=0v=0, a contradiction.

So there are three possible solutions, namely f(x)=xf(x)=x for all xRx\in \mathbb{R}, f(x)=xf(x)=-x for all xRx\in \mathbb{R}, and f(x)=0f(x)=0 for all xRx\in \mathbb{R}. It is easy to check that all three are valid solutions of the given equation.

Miles Koumouris - 4 months ago
×

Problem Loading...

Note Loading...

Set Loading...